Bioprocess of of Astaxanthin Production as Functional Food from Aurantiochytrium Microalgae: A Review - Suhendra Suhendra (CHEMICA: Jurnal Teknik Kimia, 2021)
The Covid-19 pandemic has increased human needs for nutrition including functional food and nutraceutical products in line with the need to boost immunity to resist viral infection, maintain a healthy life, and limit fatalities. In this regard, the choice to use functional food and nutraceuticals seems to be a promising panacea. This paper aims to examine the potential of the microalgae species Aurantiochytrium, which is commonly found in the mangrove ecosystem. This microalgae species has received a lot of attention from researchers because of its high content of lipids and other high-value-added components as well as its fast growth and resistance to environmental stress. With current bioprocess technology, Aurantiochytrium microalgae can be deployed to produce high-value-added components such as astaxanthin. During the current pandemic, the need for this product is increasing as raw material for drugs, health supplements, antioxidants, and vaccine adjuvants that are in direct contact with efforts to combat the human coronavirus and prevent the spread of viral diseases. In general, producing functional nutritional products from Â Aurantiochytrium microalgae requires several stages starting from the isolation and screening of microalgae, cultivation, extraction of the desired components and finally downstream processing for purification and packaging the product. Although Aurantiochytrium microalgae is found in the mangrove ecosystem, unfortunately, studies on the production potential of functional nutrients from microalgae Aurantiochytrium native strains from Indonesia have been rarely pubslihed. Therefore, it is expected that this study will become a fundamental basis for further research in this field and increasing attention for the production of functional nutrients from Â Aurantiochytrium microalgae isolated from mangrove forests in Indonesia. An early insight into bioprocess technology modes such as appropriate isolation techniques, cultivation, and extraction to produce astaxanthin is provided.